The information system of the French Peatland Observation Service: Service National d'Observation Tourbières – A valuable tool to assess the impact of global changes on the hydrology and biogeochemistry of temperate peatlands through long term monitoring. Issue 6 (8th June 2021) - Gogo, Sébastien; Paroissien, Jean‐Baptiste; Laggoun‐Défarge, Fatima; Antoine, Jean‐Marc; Bernard‐Jannin, Léonard; Bertrand, Guillaume; Binet, Philippe; Binet, Stéphane; Bouger, Guillaume; Brossard, Yohann; Camboulive, Thierry; Caudal, Jean‐Pierre; et al.
Abstract: Mitigating and adapting to global changes requires a better understanding of the response of the Biosphere to these environmental variations. Human disturbances and their effects act in the long term (decades to centuries) and consequently, a similar time frame is needed to fully understand the hydrological and biogeochemical functioning of a natural system. To this end, the 'Centre National de la Recherche Scientifique' (CNRS) promotes and certifies long‐term monitoring tools called national observation services or 'Service National d'Observation' (SNO) in a large range of hydrological and biogeochemical systems (e.g., cryosphere, catchments, aquifers). The SNO investigating peatlands, the SNO 'Tourbières', was certified in 2011 (https://www.sno-tourbieres.cnrs.fr/ ). Peatlands are mostly found in the high latitudes of the northern hemisphere and French peatlands are located in the southern part of this area. Thus, they are located in environmental conditions that will occur in northern peatlands in coming decades or centuries and can be considered as sentinels. The SNO Tourbières is composed of four peatlands: La Guette (lowland central France), Landemarais (lowland oceanic western France), Frasne (upland continental eastern France) and Bernadouze (upland southern France). Thirty target variables are monitored to study the hydrological and biogeochemical functioning of the sites. They are grouped into four datasets: hydrology, fluvial export of organic matter, greenhouse gas fluxes and meteorology/soil physics. The data from all sites follow a common processing chain from the sensors to the public repository. The raw data are stored on an FTP server. After operator or automatic processing, data are stored in a database, from which a web application extracts the data to make them available (https://data-snot.cnrs.fr/data-access/ ). Each year at least, an archive of each dataset is stored in Zenodo, with a digital object identifier (DOI) attribution (https://zenodo.org/communities/sno_tourbieres_data/ ).